PENGUATAN KAPASITAS ADAPTIF DAN DAYA SAING UMKM MELALUI PENDAMPINGAN TRANSFORMASI DIGITAL BERKELANJUTAN - Ovina Salsabila; Putri Jamilah; Novie Kurniasih; Hanina Maulida; Fera Putri Dea (Jurnal Edukasi Pengabdian Masyarakat, 2026)
Digital transformation has become a key strategy for enhancing the adaptive capacity and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) amid the rapid development of the digital economy. However, many MSMEs still face challenges in utilizing digital technologies, particularly in adopting cashless payment systems, digital marketing, and online marketplace platforms. This community service program aimed to strengthen the adaptive capacity and competitiveness of MSMEs through sustainable digital transformation assistance. The program employed observation, interviews, socialization, training, mentoring, as well as monitoring and evaluation involving 12 MSMEs located in Kampung Tengah and Pisangan, East Jakarta. The assistance focused on implementing the Quick Response Code Indonesian Standard (QRIS) as a digital payment system, optimizing digital marketing through social media, and integrating eligible MSMEs with the ShopeeFood platform. The results indicated that all participating MSMEs successfully adopted QRIS as a digital payment method, while several MSMEs improved their capacity to manage digital promotional content and expanded their market reach through digital platforms. Sustainable assistance proved effective in enhancing digital literacy, improving transaction efficiency, and strengthening MSMEs' readiness to adapt to the evolving digital economy.